Rifaximin potentiates clarithromycin against Mycobacterium abscessus in vitro and in zebrafish - Goh, Boon Chong (2024)
Mycobacterium abscessus is a non-tuberculous mycobacterium (NTM) that causes chronic pulmonary infections. Because of its extensive innate resistance to numerous antibiotics, treatment options are limited, often resulting in poor clinical outcomes. Current treatment regimens usually involve a combination of antibiotics, with clarithromycin being the cornerstone of NTM treatments.